THE REPRODUCTIVE PERFORMANCE OF BALI CATTLE AND IT’S GENETIC VARIATION - Sri Rahayu (JURNAL PENELITIAN BIOLOGI BERKALA PENELITIAN HAYATI, 2014)
Bali cattle ( Bos sondaicus ) is one of the Indonesia native cattle which is the result of wild banteng domestication. The advantages of Bali cattle, among others, are having a high fertility rate (80-82 %) and good adaptability to the new environment. It was found that there are genetic variation in several genes associated with reproductive function in Bali cattle. Some studies have reported an association between genetic variation in reproductive function of cattle. However, studies on the correlation between genetic variation reproductive genes with reproductive performance of Bali cattle are still low. This article aims to provide an overview of Bali cattle genetic variation reproductive genes and making it possible as candidate marker for selection and improving reproductive performance of Bali cattle.